PELAKSANAAN PEMBANGUNAN KONSTRUKSI DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Bha'iq Roza Rakhmatullah; Achmad Irwan Hamzani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The implementation of construction development in land acquisition is carried out after the stages of land acquisition, namely: the planning stage, the preparation stage, the implementation stage and the stage of handing over the results of land acquisition. However, in reality there is construction implementation prior to the four stages of land acquisition. An example is the construction of the Tefmo Dam in South Central Timor Regency and the construction of the Tefmo Dam in Kupang Regency, East Nusa Tenggara Province. The problem examined in this study is how the implementation stages of construction development in land acquisition for public purposes and what are the legal consequences for the implementation of construction development that precedes the stages of land acquisition. The method used in this research is normative juridical. The results of this study provide an answer that the implementation of construction development in land acquisition is carried out after the stages of land acquisition. This is carried out as a form of legal protection for the community regarding their land rights. Then, the legal consequence of the construction that was carried out prior to the land acquisition stage was that the National Land Agency could not carry out an inventory and identification and the Land Assessment Team could not carry out an assessment of land objects because the land objects had been evicted and flattened, so that compensation could not be carried out. Therefore, the National Land Agency and related agencies need to coordinate to make a work map, there needs to be law enforcement and the government must find a solution with all its efforts so that the community receives compensation.Keywords: Construction Development; Land Acquisition; Legal Consequences AbstrakPelaksanaan pembangunan kontruksi dalam pengadaan tanah dilaksanakan setelah tahapan-tahapan pengadaan tanah, yaitu: tahapan perencanaan, tahapan persiapan, tahapan pelaksanaan dan tahapan penyerahan hasil pengadaan tanah. Akan tetapi dalam kenyataannya terdapat pelaksanaan pembangunan kontruksi mendahului keempat tahapan pengadaan tanah. Sebagai contoh adalah pembangunan Bendungan Temef di Kabupaten Timor Tengah Selatan dan Pembangunan Bendungan Tefmo di Kabupaten Kupang Provinsi Nusa Tenggara Timur. Masalah yang diteliti dalam penelitian ini adalah bagaimana tahapan pelaksanaan pembangunan kontruksi dalam pengadaan tanah untuk kepentingan umum dan bagaimana akibat hukum terhadap pelaksanaan pembangunan kontruksi yang mendahului tahapan pengadaan tanah. Metode yang digunakan dalam penelitian ini adalah yuridis normatif. Hasil penelitian ini memberikan jawaban bahwa Pelaksanaan pembangunan kontruksi dalam pengadaan tanah dilaksanakan setelah tahapan-tahapan pengadaan tanah. Hal ini dilaksanakan sebagai bentuk perlindungan hukum kepada masyarakat akan hak atas tanahnya. Kemudian, akibat hukum dari Pembangunan kontruksi yang dilaksanakan mendahului tahapan pengadaan tanah adalah Badan Pertanahan Nasional tidak bisa melaksanakan inventarisasi dan identifikasi serta Tim Penilai Pertanahan tidak dapat melakukan penilaian atas objek tanah karena objek tanah telah digusur dan rata, sehingga tidak bisa dilaksanakan pemberian ganti rugi. Oleh karena itu, Badan Pertanahan Nasional dan Instansi terkait perlu berkoordinasi membuat peta kerja, perlu adanya penegakan hukum dan Pemerintah Harus mencarikan solusi dengan segala upaya agar masyarakat menerima ganti kerugian.Kata Kunci: Pembangunan Kontruksi; Pengadaan Tanah; Akibat Hukum